Pengaruh Kualitas Pelayanan Pajak dan Penerapan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Kosambi - Tangerang - Ariesta, Cindy; Suryaningsih, Rosita (Ultimaccounting Jurnal Ilmu Akuntansi, 2013)
Tax revenue has a significant role for Indonesia towards the state expenditure budget every year. The purpose of this research is to analyze the influence of tax service quality and tax penalties towards individual tax payer's compliance. Objects in this study are the individual tax payers who are listed in Tax Service Office (Kantor Pelayanan Pajak) Kosambi - Tangerang. The samples are selected by Convenience Sampling Method. Data sources used in the form of primary data and techniques of data collection is done by distributing the enclosed questionnaire instruments that have been given a score. The results of this study are (1) Tax Service Quality has significant impact towards individual tax payer's compliance, (2) Tax Penalties has significant impact towards individual tax payer's compliance. Key word: Tax Service Quality, Tax Penalties, Tax Payer's Compliance